Air Quality Over Baghdad City Using Ground and Aircraft Measurements. - F.Khanjer, Ebtesam; A.Yosif, Mohammed; A.Sultan, Mathem (Iraqi Journal of Science, 2023)
In this paper, the air pollutants concentrations measurements such as TotalSuspended Particles(TSP), Carbon Monoxides(CO),Carbon Dioxide (CO2) andmeteorological parameters including temperature (T), relative humidity (RH) andwind speed & direction were conducted in Baghdad city by several stationsmeasuring numbered (22) stations located in different regions, and were classifiedinto (industrial, commercial and residential) stations. The results show that theconcentrations of pollutants (TSP, CO, and CO2) have exceeded the air qualitystandards set by World Health Organization (WHO) and Iraqi limitation in thestations of the Baghdad city. The program (ArcGIS) used to prepare maps of airpollution in Baghdad city, as well as MS Excel used for drawing the concentrationsof pollutants in ground and to show changed the concentrations with altitude.Aircraft measurements of gaseous pollutants including ozone (O3), Carbonemonoxide (CO) , Carbone dioxide (CO2) and the particulate matter concentrations (PM10 , PM2.5 ) were conducted in the Baghdad city from ( 2 January 2014 to 4Mars 2014 ),the data of total 10 flight (22 h flight time ),the vertical profile of (CO,CO2 ,O3 ,PM10and PM2.5 ) have been obtained at different altitude over theBaghdad city covering the lowermost troposphere up to 2100 feet altitude aboveground level (AGL) during all flights were obtained by A bell 407 aircraft and Aking aircraft. The objective was to characterize the spatial and vertical distributionsof these air pollutants.The results indicate that the air pollution levels were severeover the Baghdad city. The pollutants concentrations were generally decreasingwith altitude in the boundary layer in the flight measurements .These results arevaluable for studying vertical distribution characteristics of gaseous pollutants andparticulate matters in the boundary layer over the Baghdad city and for providingimportant basic data to environmental assessment and decision-making. The reasonsfor this increasing due to increase in anthropogenic emissions, mainly due to theincrease in fossil fuel use for heating, the burning of the fuel used in various typesof vehicles, as well as the low quality of fuel and the age of the vehicles, the use ofgenerators, the dry climate, soil erosion, lack of roadside vegetation, paved areas,substantial rise in number of vehicles and poorly maintained vehicles have all beenheld Responsible.